Behavior of men with STD who have been treated in a health care unit of STD reference in Fortaleza - Araújo, Maria A L; Diógenes, Sérgio; Silva, Raimunda Magalhães da (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the STDs became relevant with the advent of AIDS because they work as a doorway through which the HIV virus can get in. Itsdetection and early treatment is important to control an AIDS outbreak. Objective: to present the sexual behavior of men with STD who were treat-ed in a Health Care Unit of STD reference in Fortaleza – Ce. Methods:this is a quantitative study which was carried out from May to June, 2003.The sample of the population is formed by 60 men who were diagnosed with STD. The study used the Epi-Info for organization and analysis of thedata and it was approved by the Ethics committee. Results:the STDs prevailed in the group from 18 to 29 years of age, 36 (60%) of them have saidthat in the last 3 months they had the same sexual partner, 32 (53.3%) of them had eventual partners. None of them have mentioned the use of intra-venous drugs and 38 (63%) used to drink alcohol. 24 (40%) of them all waited over a month to look for help after they had observed the symptoms.18 (30%) had first gone to other places before they looked for the Health Care Unit. The majority of them, 54 (90%) of the men have mentioned het-erosexual relationships and 15 (25%) have stated having homosexual relationships. The most frequent sexual practice vaginal/anal, 26 (43.3%) and58 (96.9%) respectively, did not use condoms in the sexual intercourse before the diagnosis of STD. After they had begun the treatment, 38 (63.3%)of the men have mentioned always using the condom in their sexual intercourse. Conclusion: it is necessary to better the service and the developmentof health education strategies with men, families and community.